APLIKASI THEORY VIRGINIA HENDERSON DALAM ASUHAN KEPERAWATAN PADA KASUS POST-SECTIO CAESARIA - Yulianti, Dian Anggur; Irna Nursanti (CV. ADIBA ADISHA AMIRA, 2024)
This study evaluated the impact of Sectio Caesarean delivery on the mother, showing that the risk of complications is five times higher than normal delivery. Sectio Caesarea causes postoperative pain and wounds, restricting the patient's movement and leading to stiff joints, poor posture, muscle contractures, and slow wound healing. Virginia Henderson's theory is the basis for nurses in restoring patient independence, focusing on 14 basic human needs. The case study of Mrs. D, a post-Sectio Caesarea patient without other complications, applied the purposive method. Data were obtained through observation, interview, and physical examination, and processed with Virginia Henderson's theory. The results showed that the application of the theory was effective in restoring the patient's independence, emphasizing the need for care based on basic human needs. The conclusion of the study confirms that Virginia Henderson's theory can be effectively applied in dealing with health problems in post-Sectio Caesarea patients.